Boys weekend - Lubchansky, Mattie (Pantheon graphic library, 2023)
"Newly-out trans artist's assistant Sammie is invited to an old friend's bachelor weekend in El Campo, a hedonistic wonderland of a city floating in the Atlantic Ocean's international waters-think Las Vegas with even fewer rules. Though they have not identified as a man for over a year, Sammie's old friends haven't quite gotten the message-as evidenced by their former best friend Adam asking them to be his "best man." Arriving at the swanky hotel, Sammie immediately questions their decision to come. Bad enough that they have to suffer through a torrent of passive-aggressive comments from the groom's pals-all met with zero pushpack from supposed "nice guy" Adam. But also, they seem to be the only one who's noticed the mysterious cult that's also staying at the hotel, and is ritually dismembering guests and demanding fealty to their bloodthirsty god. Part satire, part horror, Boys Weekend explores what it's like to exist as a transfemme person in a man's world, the difficulty of maintaining friendships through transition, and the more cult-like effects of masculinity, "hustle" culture, and capitalism-all through the vibrant lens of a surreal, scary, and immensely imaginative romp"--